Pendampingan Kewirausahaan bagi Usaha Mikro Kecil dan Menengah dari Siswa SMK, Mahasiswa dan Alumni STIE Port Numbay Jayapura: Entrepreneurship Assistance of Micro, Small and Medium Enterprises for Vocational High School Students, Students and Alumni of STIE Port Numbay Jayapura - Wa Ariadi; Muhamad Syafii; Ahadi Rerung; Terweline Tapilatu; Yendra Yendra (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Implementing community service by lecturers is one of the obligations of Tridharma Perguruan Tinggi (the three pillars of higher education practice). The implementation of a community service program through entrepreneurship assistance of Micro, Small, and Medium Enterprises for high school vocational students, students, and alums of STIE Port Numbay is expected to provide knowledge related to the management of the business being carried out, starting from financial management, the ability to introduce the business products to the community so that the implementation of their business and production continues to be sustainable, determining the right sales strategy and improving the quality of the products produced and make various models of the products as attractive as possible. For business actors who are just planning a business and those who have carried out business activities or whose businesses are already running, assistance is needed to be executed by the government, private sectors, and lecturers because it is a complete form of training and interaction built by the assistance team with Micro, Small and Medium Enterprises actors, including those who already have a business and those who want to develop their business continuously. Based on the results of communication and discussions during the assistance carried out by the STIE Port Numbay team, it is known that these business actors have limited knowledge in managing and developing the business being carried out, choosing the right business place, and marketing their business products.